Profile of the PhET Assisted Problem-Based Learning Model for Improving Critical Thinking Skills of High School Students - Beta Elok Yuanata; Dwikoranto Dwikoranto; Rahyu Setiani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This research discusses the implementation of a Problem-Based earning learning model assisted by PhET Simulation to improve students' critical thinking skills on the material of traveling waves and stationary waves. The purpose of this study is to obtain a profile of students' critical thinking skills in physics learning at the Senior High School level and to evaluate the effectiveness of the PBL model enhanced by using PhET Simulation in improving these skills. This research method is a preliminary study and descriptive qualitative. The research instruments used were a critical thinking skills test, a teacher interview, and a learner response questionnaire. The findings of students' critical thinking skills are categorized into low, medium, and high. There are 62 students in the low category and 8 students in the medium category and the level of critical thinking skills of female students is higher than male students. Based on the results obtained, it can be concluded that the critical thinking skills of students are in a low category, and practice and the use of appropriate learning models are needed.